2009
DOI: 10.1101/gr.087890.108
|View full text |Cite
|
Sign up to set email alerts
|

Integrating siRNA and protein–protein interaction data to identify an expanded insulin signaling network

Abstract: Insulin resistance is one of the dominant symptoms of type 2 diabetes (T2D). Although the molecular mechanisms leading to this resistance are largely unknown, experimental data support that the insulin signaling pathway is impaired in patients who are insulin resistant. To identify novel components/modulators of the insulin signaling pathway, we designed siRNAs targeting over 300 genes and tested the effects of knocking down these genes in an insulin-dependent, anti-lipolysis assay in 3T3-L1 adipocytes. For 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 54 publications
1
61
1
Order By: Relevance
“…After future filtering, S1pr2 gene was identified as one of key regulators of insulin signaling. Increased plasma insulin levels were detected in male S1pr2 -/-knockout mice, suggesting there is a potential link between S1pr2 and insulin resistance [37].…”
Section: Understanding Signaling Pathwaysmentioning
confidence: 96%
See 2 more Smart Citations
“…After future filtering, S1pr2 gene was identified as one of key regulators of insulin signaling. Increased plasma insulin levels were detected in male S1pr2 -/-knockout mice, suggesting there is a potential link between S1pr2 and insulin resistance [37].…”
Section: Understanding Signaling Pathwaysmentioning
confidence: 96%
“…The cell-based RNAi screens have yielded tremendous amount of novel discoveries and greatly promoted our understanding on many basic biological processes, molecular functions and complexity of cellular networks. New findings from genome-wide RNAi screens have led to the identification of novel components of canonical signaling transduction pathways, such new players of ERK pathway [16] and phosphorylation networks regulating JUN NH2-terminal kinase (JNK) pathway [36]; the role of S1pr2 gene (Sphingosine-1-phosphate receptor 2) in insulin signaling [37]; novel modulators of p53 pathway [38]; and key genes that are essential for the proliferation of cancer cells [17]. Recently, an integrative approach with RNAi screen and whole genome structural analysis identified IKBKE kinase as a breast cancer oncogene [39].…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies support the utility of analyzing network interactions in receptorspecific pathways, to generate insights into signaling mechanisms. Furthermore, they also emphasized the potential of this approach for identifying new drug targets (Tu et al 2009;Astsaturov et al 2010;Bandyopadhyay et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…27 Several studies have implemented this analysis on gene expression data and RNAi screening data. 6,46,69,72 For instance, Bredel et al 6 identified 3 novel MYC-interacting genes in human gliomas through functional network analysis of gene expression data with Ingenuity Pathways Analysis (IPA); Mori et al 46 reported that gene profiling and pathway analysis helped to elucidate the molecular mechanisms involved in neuroendocrine transdifferentiation of prostate cancer cells; and Tu et al 69 used an siRNA screening approach to identify a reliable set of components/modulators of the insulin signaling pathway. Thus, functional genomic analyses that leverage multiple types of information have begun to show promise in uncovering important biology not apparent from standard analysis methods.…”
Section: Protein-protein Interaction Network Analysismentioning
confidence: 99%